Precariousness, Gender, Resistance and Consent in the Face of Global Production Network's 'Reforms' of Pakistan's Garment Manufacturing Industry. (December 2019) - Ayaz, Muhammad; Ashraf, Muhammad Junaid; Hopper, Trevor
This case study of the restructuring of Pakistan's garment manufacturing industry explores how attempts to increase capital's control over the labour process intersect with local patriarchal structures and trigger workers' reflexivity and agency causing unanticipated consequences. Using Archer's notion of agency, the article examines the theoretical space where capitalism meets patriarchy, and both are reproduced. The focus on reflexivity, anchored between objective contexts and agents' personal concerns, helps theorize capital–labour–gender relations in global supply chains and explains workers' impactful resistance to protect a supposedly precarious work regime. Our findings challenge the notion that globalization reduces workers' agency and their potential for impactful resistance.